Fungal Diversity in Wet and Dry Ripe Plantains: Isolation, Identification, and Implications for Public Health (International Journal of Scientific Research in Science and Technology, 2024)
The persistent inadequacy of storage facilities in in globally and more prevalent in developing nations leads to substantial annual losses of harvested agricultural produce, severely impacting the economic stability of local farmers. This investigation focuses on the critical public health implications arising from the fungal contamination of stored plantain chips, a delicacy snack in Nigeria, West Africa. Notably, the fungal species isolated, which are Aspergillus flavus, Aspergillus niger, Penicillium chrysogenum, Saccharomyces cerevisiae, Aspergillus fumigatus, Fusarium spp., Rhizopus stolonifer, and Mucor spp. are critical from a public health perspective. Species such as Aspergillus flavus and Aspergillus niger are particularly concerning due to their capacity to produce aflatoxins, which are among the most carcinogenic substances known and have been linked to liver cancer and immune system suppression. The prevalence of these mycotoxins not only compromises the nutritional integrity and safety of the plantain chips but poses severe risks to consumers, highlighting a broader issue of food security and safety. This study brings to the fore the pressing need for interventions that enhance the storage conditions and decrease fungal contamination, thereby reducing the exposure of the population to mycotoxins. The implications of this research extend beyond the economic damage to encompass significant public health concerns, emphasizing the critical need for regulatory, technical, and infrastructural developments to uphold the microbial quality of plantain both in wet and dry states, ensuring safe consumption.
Keywords: Mycoflora; Plantain; Food Safety; Public Health; Aflatoxins; Fungal Contamination